Sensing Materials: Optical Sensing Based on Carbon Quantum Dots - Melo-Freire, R (Elsevier, 2022)
Fluorescent carbon quantum dots (CQDs) are carbon nanoparticles with excellent optical properties, which have found wide use in sensing platforms. In this chapter, we describe the recent advancement of CQDs and optical sensors, principally focusing in syntheses methods, luminescence-dependence of size and chemical composition, and applications in sensor arrays by chemometric techniques. In addition, we also present a discussion considering the remaining challenges and future trends in the development of fluorescents sensors. © 2023 Elsevier Ltd. All rights reserved